“Темные места” в переводе арабских и старотурецких мусульманских произведений на белорусский и польский языки в XVII в. - Мишкинене, Галина (Kalbotyra, 1997)
The article deals with problematic interpretations of the translation of Old Turkish manuscripts into Belarussian and Polish in the XVII century. The Вelarussian texts written in Arabic alphabets are not quite understandable due to the charicature of this alphabet. The author gives interpretations of the problematic cases of the manuscript KU-I446, LU-893 and Leip.-280 and translates them into Lithuanian.